Linear park in perspective of urban vitality on Arroio Corrente Beach In Jaguaruna, Santa Catarina - Martins, Júlia Zumblick; Medeiros, Claudione Fernandes de (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – To conduct a literature review including the concept and importance of urban vitality and parks in cities, highlighting how public open spaces directly affect people’s quality of life. Methodology – Theoretical framework related to Urban Vitality, Parks and Linear Parks. Studies of design references based on the following topics: context of insertion, design criteria, program and comparison with the parameters necessary for a park with vitality. In the end, a study area was delimited on Arroio Corrente beach in Jaguaruna, SC, where the following data were collected: access, location of the project site and road hierarchy, templates, full and empty spaces, urban infrastructure, legislation, bioclimatic data, constraints, potentialities and deficiencies. Based on the surveys and studies, strategies and guidelines, a needs program and an urban plan for the area were proposed. Originality/Relevance – Abandoned urban spaces without public use become degraded and unsafe spaces. The study area is environmentally sensitive because it has a stream and faces the sea. Establishing compatible uses through quality and environmentally sustainable urban planning and design is essential for the quality of the place. It is a fact that the waterfronts are being occupied and suffering from real estate speculation. Therefore, allowing public open spaces to occupy the waterfront is an important issue to be included in the Brazilian agenda. Results – he result achieved was the proposal of an urban party for the study area with the following guidelines: diversity and inclusion, density of uses and people promoting social interaction, preservation of biodiversity and the appreciation of everyday elements. Theoretical/Methodological Contributions – The study reinforces the importance of integration between natural and urban spaces, showing that the creation of urban public spaces can be an effective solution to improve quality of life. Social and Environmental Contributions – Urban vitality refers to life in public spaces. Promoting improved quality of life through accessible spaces for leisure and coexistence, which favors social inclusion, community interaction, safety, density of uses and people. Environmentally, parks play a crucial role in the preservation of natural resources, such as native vegetation and water bodies, in addition to promoting environmental awareness and the sustainable use of space, encouraging conservation practices and recovery of degraded areas.